2021
DOI: 10.5194/acp-21-13811-2021
|View full text |Cite
|
Sign up to set email alerts
|

Ice and mixed-phase cloud statistics on the Antarctic Plateau

Abstract: Abstract. Statistics on the occurrence of clear skies, ice clouds, and mixed-phase clouds over Concordia Station, in the Antarctic Plateau, are provided for multiple timescales and analyzed in relation to simultaneous meteorological parameters measured at the surface. Results are obtained by applying a machine learning cloud identification and classification (CIC) code to 4 years of measurements between 2012–2015 of downwelling high-spectral-resolution radiances, measured by the Radiation Explorer in the Far I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Satellite observations also suffer from the effect of ground clutter for observations closer to the ground (Bennartz et al, 2019). These recent cloud observations campaigns all pointed towards a higher than anticipated occurrence of SLW and mixed phase clouds (Scott and Lubin (2016); Ricaud et al, 2020;Zhang et al, 2019;Alexander et al, 2021;McErlich et al, 2021;Cossich et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Satellite observations also suffer from the effect of ground clutter for observations closer to the ground (Bennartz et al, 2019). These recent cloud observations campaigns all pointed towards a higher than anticipated occurrence of SLW and mixed phase clouds (Scott and Lubin (2016); Ricaud et al, 2020;Zhang et al, 2019;Alexander et al, 2021;McErlich et al, 2021;Cossich et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Satellite observations also suffer from the effect of ground clutter for observations closer to the ground (Bennartz et al, 2019). These recent cloud observation campaigns have all pointed towards a higher than anticipated occurrence of SLW and mixed phase clouds (Scott and Lubin, 2016;Ricaud et al, 2020;Zhang et al, 2019;Alexander et al, 2021;McErlich et al, 2021;Cossich et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors (such as Maestri et al, 2019a, Saito et al, 2020 have shown the potentialities of exploiting FIR spectrally resolved radiances to refine ice clouds microphysical and optical properties. Maestri et al (2019b) and Cossich et al (2021) also showed the benefit of using FIR channels in combination with MIR ones to largely improve the performances of cloud identification and classification (i.e., between ice and liquid water phase) algorithms.…”
mentioning
confidence: 99%